PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA DAN IMPLIKASINYA TERHADAP KETAHANAN SOSIAL BUDAYA (Studi Di Desa Wisata Brayut Pandowoharjo, Kecamatan Sleman, Kabupaten Sleman, D.I. Yogyakarta) - Hendryantoro, Anggun (Jurnal Ketahanan Nasional, 2014)
Community empowerment procesed with tourism village development at Brayut Pandowoharjo Tourism Village Sleman thoughg three levels, namely concept socialization level, ability transformation level, and gaining independence to managed the tourism village level. The research purposes were finding the village communityâs empowerment with tourism village and its implication on social culture resilience. This research was carried out with observation, interview, and analysis method and bibliography study which analyzed with deep interview system and analysis. Therefore the result of community empowerment Brayut Tourism Village should be able to involved the Brayut village communityâs participation started from the planning, conducting, and evaluating and continuing monitoring. Communityâs empowerment with tourism village development also had to strengthened social culture life as the embodiment of social culture resilience. It could be done with establishment of community institution, togetherness as the embodiment of sharing responsible, religious tolerance, custom preservation, cultural art and way of life.Keywords: Empowerment, Tourism Village Development, Social Culture Resilience.